Employees' knowledge, attitudes and practices around HIV/AIDS at Rosh Pinah Zinc Mine, Namibia. - Rukambe, Zelda (My University, 2010)
The spread of HIV/AIDS continues to increase, despite efforts committed globally, regionally and nationally to curb the impact of the HIV/AIDS pandemic (UNAIDS, 2009). Organisations are becoming more aware of the threat of the HIV/AIDS pandemic and as a result many today commit resources towards managing HIV/AIDS in the workplace through HIV/AIDS programmes. The question remains as to whether such efforts will be effective. A Knowledge, Attitudes and Practices/ Behaviour (KAPB) study is one of the tools that can be used to monitor and evaluate the effectiveness of an HIV/AIDS programme. Companies that have conducted a Knowledge, Attitude, Practice and Behaviour (KAPB) study within its workforce have found it to be a very useful practice for the development, as well as for the monitoring and evaluation, of HIV programmes (Price Waterhouse Coopers, 2007). An exploratory research design using a mixed-design approach was employed to investigate the existing knowledge, attitudes and practices related to HIV/AIDS by the workforce at the Rosh Pinah Zink Mine Corporation in Namibia. A Maasdorp (2008) standardised questionnaire was used to obtain both quantitative and qualitative information from the respondents. In addition to a small scale survey, qualitative data was collected by means of a focus group to supplement mainly quantitative questionnaire data. The questionnaire was piloted at a company in Windhoek that operates similarly to Rosh Pinah Mine. The mixture of both approaches can compliment and supplement one another on the weakness of each approach. In this way the researcher was able to gain a deeper understanding of the research problem (Punch, 2004). A stratified sample comprising of 123 out of 561 employees across the mine workforce served as respondents, while seven employees served as respondents in the focus group discussion. The information collected by means of the survey was subjected to both quantitative and qualitative data analysis, while the focus group transcripts were thematically analysed. The results of the study are intended to provide an understanding of the existing knowledge, attitudes and practices of the workforce with regards to HIV/AIDS. The study arrived at recommendations for the occupational social workers, as well as for planners of HIV/AIDS programmes at the mine in order to address identified gaps with regards to HIV/AIDS knowledge, attitudes and practices of the employees. Secondly, the study arrived at baseline information that may be used to monitor the impact of HIV/AIDS workplace programmes being implemented thereafter. This study provided the basis for a follow-up study that will compare findings of workers who have been exposed to the proposed intervention.